Analisis Produk, Kualitas Layanan, Kepercayaan Terhadap Kepuasan Dan Pengaruhnya Bagi Loyalitas Pengguna Bank BRI (Studi Kasus Pt. Bank BRI Unit Sidorame) - Ertina Lafau; Ernima Telambanua (Departement of Mathematics Education, 2023)
This research aims to determine the influence of products, service quality and trust on customer satisfaction and loyalty in using BRI Bank, at PT. BRI Bank Sidorame Unit. The population in this research is customers at PT. Bank BRI Sidorame Unit which uses Bank BRI Products. The final sample obtained was 100 respondents. The data analysis used is path analysis. The influence of products on satisfaction at PT. Bank BRI Sidorame unit has a t-count value of 4.299 > t-table 1.984, and a significant result of 0.001. Because the significant value is 0.001 < 0.05, it rejects Ho and accepts Ha. The influence of service quality on satisfaction at PT. BRI Bank Sidorame unit service quality variable has a calculated T value of 2,627 > T table 1.984, and a significant result of 0.010. because the value 0.010 < 0.05, so it rejects Ho and accepts Ha. The influence of trust on satisfaction at PT. BRI Bank sidorame unit trust variable has a calculated T value of 2.416 > T table 1.984, and a significant result of 0.018. because the value 0.018 < 0.05, so it rejects Ho and accepts Ha. The influence of products on loyalty at PT. The BRI Bank Sidorame unit product variable has a calculated T value of 2.881>T table 1.984, and a significant result of 0.005, so it rejects Ho and accepts Ha. The influence of service quality on loyalty at PT. BRI Bank Sidorame unit service quality variable has a calculated T value of 2.296 > T table 1.984, and a significant result of 0.024. because the value 0.024 < 0.05, so it rejects Ho and accepts Ha